PERILAKU BERAGAMA DAN ETOS KERJA MASYARAKAT PESISIR DI KELURAHAN PENGGOLI KECAMATAN WARA UTARA KOTA PALOPO - Hamdani Thaha; Muh Ilyas (Institut Agama Islam Negeri Palopo, 2016)
This study discussed the religious attitude and work ethos of coastal communities in the Penggoli (studies on the clumps of Lawatu). The purpose of this study is to determine the pattern of religious behavior and its relationship with work ethic of Lawatu societies. The data were collected through observation, documentation, and structured-interviews. The interviews were conducted in semi-structures by selecting the informant utilizing a purposive sampling technique. The findings showed that: 1) Lawatu societies who live in Penggoli are devout religious believers, but they also still maintain ancestors cultures transformed into religious rituals. Many rituals that have become religious traditions are still often conducted by Lawatu societies, for examples: Mabbaca-baca, Massio-sio, and Mammaulu. 2) They have lives principles in running their activities, especially in civic lives and subsistences. The principles are in the forms of Mabbulo Sibatang, Pakkareso, Mapanre Lima, Sipakatongeng.